Ransom - Malouf, David
A tale of suffering, sorrow, and redemption, "Ransom" is a retelling of one of the most famous stories in all of literature--Achilles's slaughter and desecration of Hector, and Priam's attempt to ransom his son's body in Homer's "The Iliad."